2010
DOI: 10.1111/j.1365-2133.2010.09822.x
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin null mutations increase the risk and persistence of hand eczema in subjects with atopic dermatitis: results from a general population study

Abstract: FLG null mutations were significantly associated with hand eczema (< 12 months) in subjects with atopic dermatitis. Combined atopic dermatitis and filaggrin null mutation status was strongly associated with early onset of hand eczema and hand eczema persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 28 publications
5
102
1
1
Order By: Relevance
“…Several studies have investigated whether certain fi laggrin variants might be associated with CHE in general. Some also investigated certain CHE subtypes [ 4,9,12,14,26 ] . Probably the most convincing evaluation of the possible association between hand eczema and fi laggrin null mutations was provided by a recent general population study including 3,471 adults.…”
Section: Hand Eczemamentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have investigated whether certain fi laggrin variants might be associated with CHE in general. Some also investigated certain CHE subtypes [ 4,9,12,14,26 ] . Probably the most convincing evaluation of the possible association between hand eczema and fi laggrin null mutations was provided by a recent general population study including 3,471 adults.…”
Section: Hand Eczemamentioning
confidence: 98%
“…Probably the most convincing evaluation of the possible association between hand eczema and fi laggrin null mutations was provided by a recent general population study including 3,471 adults. It showed that subjects with atopic dermatitis and fi laggrin null mutation status had a signifi cantly higher prevalence of hand eczema, as well as earlier onset of disease and higher persistence of disease when compared with subjects who did not report atopic dermatitis and who had wild-type fi laggrin status [ 26 ] . Carlsen et al found no association between, respectively, nickel allergy, polysensitization, hand eczema at fi rst appearance or occurrence of dermatitis, and fi laggrin null mutations [ 4 ] .…”
Section: Hand Eczemamentioning
confidence: 98%
“…Częstość występowania ACD u pacjentów z wypryskiem atopowym wynosi 13,6-27,4% i jest istotnie większa u kobiet [39]. Najczęstszymi alergenami były metale, głównie nikiel, rzadziej substancje zapachowe [39] i podłoża leków stosowanych miejscowo [40]. Wyprysk kontaktowy alergiczny, prowokowany głównie przez substancje zapachowe, chrom, nikiel i lanolinę, obserwowano u 14,9-64,2% dzieci chorych na AD [41][42][43][44].…”
Section: Atopowe Zapalenie Skóryunclassified
“…Allergic contact dermatitis prevalence in patients with atopic eczema was estimated at 13.6-27.4% and it was significantly higher in women [39]. Metals (especially nickel) and to a lesser extent flavorings [39] and bases of locally administered drugs were the most common allergens [40]. Allergic contact dermatitis provoked mainly by flavorings, chromium, nickel and lanolin was reported in 14.9-64.2% of the investigated pediatric population with AD [41][42][43][44].…”
Section: Atopic Dermatis and Contact Nickel Hypersensitivitymentioning
confidence: 99%
“…Recently, the key role of filaggrin (FLG) proteins in maintaining an effective skin barrier against the external environment has been demonstrated [20]. A positive association between FLG mutations and contact sensitivity (CS) to nickel was found among German adults [21], but could only be confirmed in Danish adults without ear piercings [22]. Furthermore, FLG mutation carriers reported ACD to nickel at a significantly younger age than controls with normal filaggrin, and they also displayed stronger patch test reactivity [23].…”
Section: Factors That May Influence the Association Between Ad And Comentioning
confidence: 99%